Feedback-Rich Model for Assessing Feed-In Tariff Policy - Salman, Ahmad; Razman, Mat Tahar (Taylor & Francis, 2014)
The depletion of fossil fuels, environmental concerns, and security of supply risk has put an emphasis on renewable sources of electricity generation. However, the high cost of technology has compelled countries to develop support policies. Feed-in tariff (FIT), which has been successful in many countries, is one such policy. In this study, a qualitative model is presented. This model takes a holistic perspective in developing renewable power infrastructure. To do this, this model takes into account social, environmental, learning effect, and the FIT policy in scaling up the renewable energy capacity. The shortcomings of the FIT policy are highlighted along with improvements in policy structure. Developed from policy makers’ perspective, this model also incorporates investors’ perception of renewable market, in a Malaysian context. Modified structure suggests making the reduction in the FIT price a variable. An additional source of income—by introducing carbon tax on fossil fuel-based generation—is suggested. Furthermore, the government’s policy target has to be made variable subject to support funds availability. The developed model’s aim is to determine whether or not the goal of transforming electricity supply chain using FIT is achievable. This model also aims to show that the qualitative model would serve as a tool for future dialogue and policy improvements.